HUBUNGAN PROKRASTINASI AKADEMIK DAN KETERLIBATAN DALAM ORGANISASI DENGAN PERFORMA AKADEMIK MAHASISWA PENDIDIKAN AKUNTANSI FKIP UNS - Kamila Luthfia Yahya; Siswandari Siswandari (Universitas Sebelas Maret, 2024)
Abstract This research aims to obtain empirical evidence about (1) the relationship between academic procrastination with academic performance; (2) the relationship between involvement in organizations with academic performance; (3) the relationship between academic procrastination and involvement in organizations with academic performance. This research uses quantitative descriptive data methods with survey research type. The population in this study was 229 FKIP UNS Accounting Education students, sampling using proportionate stratified random sampling of 146 students. Based on the research results, it can be concluded that (1) there is a negative and significant relationship between academic procrastination with academic performance as evidenced by t0 = |-2.276| with a significance level 0.007; (2) there is a positive and significant relationship between involvement in organizations with academic performance as evidenced by the value of t0 = 3.360 with a significance of 0.001; (3) there is a significant relationship between academic procrastination and involvement in organizations with academic performance as evidenced by the results of the multiple correlation test where the significance value of the F test is 0.000. The regression equation model for these three variables is Y=3.451-0.009X1+0.007X2.Keywords: Academic Procrastination, Involvement in Organizations, Academic Performance Abstrak Penelitian ini bertujuan untuk mendapatkan bukti empiris tentang (1) hubungan antara prokrastinasi akademik dengan performa akademik; (2) hubungan antara keterlibatan dalam organisasi dengan performa akademik; (3) hubungan antara prokrastinasi akademik dan keterlibatan dalam organisasi dengan performa akademik. Penelitian ini menggunakan metode kuantitatif deskriptif data dengan jenis penelitian survei. Populasi dalam penelitian ini sebanyak 229 mahasiswa Pendidikan Akuntansi FKIP UNS pengambilan sampel menggunakan proportionate stratified random sampling sebanyak 146 mahasiswa. Berdasarkan hasil penelitian, dapat disimpulkan bahwa (1) terdapat hubungan negatif dan signifikan antara prokrastinasi akademik dengan performa akademik dibuktikan dengan perolehan t0 = |-2,276| dengan signifikansi 0,007; (2) terdapat hubungan positif dan signifikan antara keterlibatan dalam organisasi dengan performa akademik dibuktikan dengan perolehan t0 = 3,360 dengan signifikansi 0,001; (3) terdapat hubungan yang signifikan secara bersama antara prokrastinasi akademik dan keterlibatan dalam organisasi dengan performa akademik dibuktikan dengan hasil uji korelasi berganda dimana nilai signifikansi uji F sebesar 0,000. Model persamaan fungsi garis regresi dari ketiga variabel tersebut adalah Y=3,451-0,009X1+0,007X2.Kata kunci: Prokrastinasi Akademik, Keterlibatan dalam Organisasi, Performa Akademik